2022
DOI: 10.3390/atmos13081247
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Gas-Phase Reaction of Nopinone with OH Radicals: Experimental and Theoretical Study

Abstract: Monoterpenes are the most essential reactive biogenic volatile organic compounds. Their removal from the atmosphere leads to the formation of oxygenated compounds, such as nopinone (C9H14O), one of the most important first-generation β-pinene oxidation products that play a pivotal role in environmental and biological applications. In this study, experimental and theoretical rate coefficients were determined for the gas-phase reaction of nopinone with hydroxyl radicals (OH). The absolute rate coefficient was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The kinetics for the H-atom abstraction sites were calculated at the M06-2X/6-311+G(d,p) level of theory for all the H-abstraction sites using the CVT/SCT method. Several previously reported theoretical studies 8,28,42,43 of atmospheric reactions showed that the M06-2X method gives more reliable kinetic results comparable with experimental studies. Therefore, herein, we have used the M06-2X method to calculate the rate coefficients.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The kinetics for the H-atom abstraction sites were calculated at the M06-2X/6-311+G(d,p) level of theory for all the H-abstraction sites using the CVT/SCT method. Several previously reported theoretical studies 8,28,42,43 of atmospheric reactions showed that the M06-2X method gives more reliable kinetic results comparable with experimental studies. Therefore, herein, we have used the M06-2X method to calculate the rate coefficients.…”
Section: Resultssupporting
confidence: 69%
“…The reaction energies obtained using the M06-2X, ωB97X-D, MP2 and CCSD(T) levels of theory are similar. As is well known from previous studies 8,22,27–29 M06-2X predicts accurate thermochemistry; herein, the discussions are based on the M06-2X method. The initial reaction of LK started from the reactant (R) to form the pre-reactive complex (RC) with an intermolecular hydrogen bond O25–H26⋯O10 in the form of a barrierless reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies show that DFT is the most accurate and cost effective method for predicting thermodynamic and kinetic properties. 18,20,21 Due to the high computational cost, G3B3 22 calculation is performed only for the most favourable initial reaction. Each local minimum is confirmed with positive frequency whereas the transition state structures are identified solely with one imaginary frequency.…”
Section: Computational Detailsmentioning
confidence: 99%